ANALYSIS OF THE FACTORS DETERMINING THE AUDIT FEE - Kusharyanti Kusharyanti (Universitas Hayam Wuruk Perbanas, 2013)
There are some factors considered to have an effect on the audit fee amount. These are importantfor the researchers to analyze. This research aimed to test the determinants of auditfee in companies that are listed on Indonesian Stock Exchange (ISE). The samples of thisstudy were 60 companies in period 2010-2011. The data was taken from annual report of thecompany. The hypothesis was tested by linier regression which consisted of two variables.First variable was dependent variable that was audit fee. The second variables were independentvariables which consist of client size, audit complexity, audit risk, company size, clientfinancial condition, audit committee characteristic, and auditor tenure. The result of thestudy shows that there are three significant independent variables influencing the audit feei.e. client size, audit complexity, and audit risk. The rest of independent variables are not significant.